(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
The study investigated the rate of litter decomposition in three prominent litter releasing indigenous tree species in the natural rainforest and an exotic species Teak, Tectona grandis Lim., in the adjacent plantation in Akure forest reserve, southwestern Nigeria. Results showed that teak had the highest litter decomposition rate and Mansonia altissima the least. There was no relationship between the rates of decomposition among all species examined. The implication is that teak litter had the highest probability of releasing litter nutrients into the soil nutrient pool than any of the selected indigenous tree species while Mansonia altissima had the least. However all species had high decomposition rates. This implies that soil fertility will be maintained if any of the tree species were to be used for monoculture plantations. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13069 Bangladesh J. Sci. Ind. Res. 47(3), 333-338 2012